If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 41 Reorder the terms: -1 + 6x = 41 Solving -1 + 6x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6x = 41 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = 41 + 1 6x = 41 + 1 Combine like terms: 41 + 1 = 42 6x = 42 Divide each side by '6'. x = 7 Simplifying x = 7
| 3(h-4)+5=60 | | 13x+2x=-150 | | 5m+42=11m | | (4x)*2=16 | | 5(8x-4)=44x | | 2-(x+5)=4x-8 | | 3(x+8)=33 | | 6(6n+7)=7(6n+6)+5 | | 7x-x=36 | | 5w+10=0 | | 6x-5y=9 | | 16(x+2)=4(4x+1)+28 | | -20y=120 | | 6x=32-2x | | 40=18x-10x | | -3(x+5)+5x=10 | | 10x^2+7x-5=0 | | 6+x=32-x | | 9x-x=40 | | 5x+2(x+8)-6(4x-5)= | | -3x^2+7x=-10 | | 8xy+6yz-4xz-8xy= | | -47-18=13a | | -1(z-6)=-20 | | -7+8x=19x+15 | | -p=2 | | -6x+9=3x-27 | | (y+3)(y+5)= | | (3b^3+9b^2-3)+(2b^3-9b+7)= | | (15-7)x=(11+5)x | | -9=9(y+3) | | 3x+4(2-x)=4x+5 |